The notions of irreducible ideals of the endomorphism ring on the category of rings and the category of modules - Hasnani, Fitriana; Fatimah, Meryta Febrilian; Puspita, Nikken Prima (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Let R commutative ring with multiplicative identity, and M is an R-module. An ideal I of R is irreducible if the intersection of every two ideals of R equals I, then one of them is I itself. Module theory is also known as an irreducible submodule, from the concept of an irreducible ideal in the ring. The set of R - module homomorphisms from M to itself is denoted by EndR(M). It is called a module endomorphism M of ring R. The set EndR(M) is also a ring with an addition operation and composition function. This paper showed the sufficient condition of an irreducible ideal on the ring of EndR(R) and EndR(M)